Relationship between Charlson comorbidity index, early recovery and 2-year mortality in elderly patients undergoing surgical treatment of inter-trochanteric fractures: a retrospective analysis - Xu Jianda (Nature Portfolio, 2021)
Abstract The aim of this study was to evaluate how the Charlson Comorbidity Index (CCI) scores contribute to early recovery and 2-year mortality in elderly patients undergoing surgical treatment of inter-trochanteric fractures. 60 cases with unilateral intertrochanteric fracture were retrospectively analyzed and divided into Low-CCI group (CCI: 1–4) or high-CCI groups (CCI: 5–6). All the patients’ electronic hospital records were reviewed. The preoperative situations (demographic data, comorbidities and fracture conditions), perioperative situations (wait time, operation time, implant choice, blood loss, transfusion or not) and postoperative situations (complications, first time out of bed, function about 1-/2- week and 2-year mortality) were recorded. 51.67% were in low-CCI group and 48.33% in high-CCI group. The survival rates in low- and high-CCI group were 93.5% and 86.2% respectively. According to the functional results of 1- or 2- week after operation, no significant difference was found (P = 0.955, 0.140). Log-rank analysis showed that the main prognostic factors were blood loss, first time out of bed and complication (P < 0.05). Multivariate analysis confirmed that complication and first time out of bed were significant factor on survival rate (P = 0.029, 0.010). Charlson comorbidity index maybe not the indicator of 2-year mortality in older patients with intertrochanteric fractures. In order to improve the prognosis, more attentions should be paid to reduce the complications and encourage postoperative earlier excise out of bed.